A STUDY OF CASTING DIE DESIGN OF BRAKE MASTER CYLINDER USING SOFTWARE SIMULATION - Nanang Ali Sutisna; Budi Sutrisno (President University, 2022)
The die design process for casting requires repeated testing in order to get a good die and produce a product that is as planned, which takes a long time and costs a lot for die making in this trial. The purpose of this study is to determine a more efficient process in die design by conducting a casting analysis using a MagmaSoft simulation. The sample part used in this study is a motorcycle brake master cylinder which will be made by the Gravity Casting process with aluminum material. The basic method used is die design using CAD by calculating Shrinkage allowance, and casting simulation using MagmaSoft software to find out various possible defects during the casting process, such as filling, air trap, solidification, hot spots, and shrinkage porosity. The simulation results show that in the filling process there is no indication of cold shot and no air trap problem, solidification and hot spots are good and occur in the part area, and there is little porosity. In general, the simulation results show that the die design has met the requirements, although there is porosity, this porosity occurs in the area that will be lost after the machining process